Estimation of Solar Hot Water System Operation for a Residential Building - Olena Savchenko; Zenon Savchenko (Energy Engineering and Control Systems, 2021)
Solar hot water supply systems can provide a significant part of the thermal energy needed in the residential sector. The use of solar hot water supply systems can reduce the consumption of traditional energy sources and, consequently, reduce greenhouse gas emissions. The aim of this article is to assess the operation of the solar heating system operation to provide the needs of the hot water supply system of a residential building with thermal energy. The efficiency of a flat solar collector operating in a single-circuit thermosyphon system of solar heating of a residential building in Lviv has been established. The solar fraction of the hot water supply system of a residential building is determined depending on the volume of hot water consumed, in particular 50, 60, 70, 80, 90, 100 l/day. It is established that the lower the need for hot water, the greater the solar fraction of the solar hot water supply system. Thus, the average annual solar fraction of the solar hot water supply system with a daily consumption of 50 l/day is 0.77, and with a daily consumption of 100 l/day the solar fraction is 0.39. The average value of the solar fraction for the solar hot water supply systems of the studied house is 0.55.